“MARGANEC TOPARSHASÍ ELEMENTLERI” TEMASÍN ÚYRENIWDE INTERAKTIV USÍLLARDAN PAYDALANÍW - Kamalova, M.O.; Aytbaeva, X.B.; Aymurzaeva, L.G. (ILIM hám JÁMIYET, 2024)
This article presents the authors’ works and suggestions on organizing classes using the "Why and How" scheme in chemistry lessons. These methods enhance students’ creativity and activity.